Microtubule-Binding Natural Products for Cancer Therapy - Yue, Qing-Xi; Liu, Xuan; Guo, De-An (Planta Medica, 2010)
Natural products, especially microtubule-binding natural products, play important roles in the war against cancer. From the clinical use of vinblastine in 1961, paclitaxel in 1992, to ixabepilone in 2007, microtubule-binding natural products have continually contributed to the development of cancer therapy. The present review summarizes the development of representative microtubule-binding natural products including agents binding to the colchicine-binding site, the Vinca alkaloid-binding site, the taxane-binding site and other binding sites. Future directions for the development of new anticancer microtubule-binding natural products are discussed. Finding new formulations, new targets and new sources of microtubule-binding natural products may enable more members of this kind of agent to be introduced into the clinic for cancer therapy.
Keywords: natural products; microtubule-binding agents; cancer; antiangiogenisis; drug resistance; marine sources